(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the clinical profile, etiological spectrum and bone marrow findings of patients presenting with pancytopenia. Patients and Methods: This was the cross sectional observational study conducted in the Department of Pathology, Hematology Section, Bolan Medical Complex, Teaching Hospital Quetta spanning over a period of five years from January 2009 to January 2014. Four hundred and two patients fulfilled the criteria of pancytopenia. Routine complete blood count (CBC), peripheral blood smear (PBS) and bone marrow aspirations (BMAs) done on all patients. Bone marrow trephine biopsies (BMTBs) were done where needed. These procedures were performed according to standard methods. SPSS-11 was used to analyze the data. Results: Out of 402 patients 32.8% were of megaloblostosis, 25.4% hypocellular marrow, 11.4% normocellular marrow, 5.2% acute lymphoblastic leukemia (ALL) and visceral leishmaniasis (VL) each, 4.5% mixed deficiency anemia (MDA), 0.8% acute myeloid leukemia (AML), malaria 2.7%, idiopathic thrombocytopenic purpra (ITP) 2.8 and 1.5% hypersplenism. Male to female ratio was 1.4:1. The commonest presenting complaint was pallor (69.52%), fever (27.20%) bleeding manifestations (15.6%), bleeding with fever (9.9%) and others. Conclusion: Complete blood count, peripheral blood smear and bone marrow aspiration and in some cases bone marrow trephine biopsies are of paramount importance in diagnosing patients with pancytopenia. As a large number of pancytopenic patients are having benign and reversible causes, an early and prompt diagnosis is mandatory for the purpose of making appropriate therapeutic decisions.